Unguarded liabilities: Borrelia burgdorferi’s complex amino acid dependence exposes unique avenues of inhibition - Holly, Katrina J.; Kataria, Arti; Flaherty, Daniel P.; Groshong, Ashley M. (Frontiers in Antibiotics, 2024)
Recent reports from the CDC approximate 500,000 cases of Lyme disease in the United States yearly, a significant economic burden on the healthcare system. Standard treatment for Lyme disease includes broad spectrum antibiotics, which may be administered for extensive periods of time and result in significant impacts to the patient. Recently, we demonstrated that Borrelia burgdorferi, the causative agent of Lyme disease, is uniquely dependent upon peptide acquisition via an oligopeptide transport (Opp) system. This dependence appears unique to the spirochete; thus, the Opp system may constitute a novel and specific target for inhibition of B. burgdorferi. For proof of concept, we conducted a pilot screen to determine if the Opp system constitutes a viable inhibitor target. OppA2 was utilized as our target protein, as it is the most prolific peptide binding protein throughout the enzootic cycle. We validated a thermal shift assay (TSA) to detect ligand binding against OppA2 and performed a high throughput screen of 2,240 molecules from a diversity set library. TSA results identified eight compounds (C1-8) demonstrating potential binding to OppA2, and growth assays identified C2 and C7 as inhibitors of B. burgdorferi growth. We confirmed by TSA that these two compounds interact with additional B. burgdorferi OppAs, potentially resulting in a cumulative inhibitory effect. Additionally, we showed that these compounds have no effect on Escherichia coli, a bacterium that encodes a dispensable Opp system which serves only as an ancillary nutrient transporter. These data demonstrate that the Opp system of B. burgdorferi acts as a viable drug target, with the potential for targeting multiple OppAs with a single compound. Moreover, the lack of inhibition against E. coli suggests that selective targeting of B. burgdorferi via the Opp system may be possible.